Non-Invasive Monitoring of Oxygen Tension and Oxygen Transport Inside Subcutaneous Devices After H2S Treatment. (30th January 2020) - Najdahmadi, Avid; Smink, Alexandra M.; de Vos, Paul; Lakey, Jonathan R.T.; Botvinick, Elliot
Medical devices for cell therapy can be improved through prevascularization. In this work we study the vascularization of a porous polymer device, previously used by our group for pancreatic islet transplantation with results indicating improved glycemic control. Oxygen partial pressure within such devices was monitored non-invasively using an optical technique. Oxygen-sensitive tubes were fabricated and placed inside devices prior to subcutaneous implantation in nude mice. We tested the hypothesis that vascularization will be enhanced by administration of the pro-angiogenic factor hydrogen sulfide (H2 S). We found that oxygen dynamics were unique to each implant and that the administration of H2 S does not result in significant changes in perfusion of the devices as compared with control. These observations suggest that vascular perfusion and density are not necessarily correlated, and that the rate of vascularization was not enhanced by the pro-angiogenic agent.